Maternal, paternal, and neonatal risk factors for neural tube defects: A systematic review and meta-analysis. Issue 78 (November 2019) - Jia, Shanshan; Wei, Xiaowei; Ma, Ling; Wang, Yanfu; Gu, Hui; Liu, Dan; Ma, Wei; Yuan, Zhengwei
Highlights: 45 studies are included in the systematic review and meta-analysis. 12 maternal, paternal, and neonatal potential risk factors on neural tube defects. Contributing to prenatal care education and public health policy. Abstract: Objective: Neural tube defects [NTDs] are severe congenital anomalies. The etiology of NTDs is not fully known, and studies on the potential risk factors of NTDs present inconsistent results. Thus, we conducted a systematic review and meta-analysis to investigate the maternal, paternal, and neonatal risk factors for NTDs. Study design: We systematically reviewed relative original studies published through October 6, 2018 available in Pubmed, Embase and the Cochrane Library without restrictions for language. The selected studies measured maternal, paternal, and neonatal risk factors and examined their associations with NTDs. A meta-analysis, including subgroup analysis and sensitivity analysis, was conducted to estimate the pooled effect measures. Two reviewers independently extracted data using a predesigned data collection form. Results: Forty-five studies were eligible for inclusion in the meta-analysis, and twelve potential risk factors were analyzed. The factors that were associated with NTDs risk included stressful life events [odds ratio [OR], 1.61; 95% confidence interval [CI], 1.24―2.08; p  < 0.001; I 2  = 59.2%], low maternal education level [OR, 1.42; 95% CI, 1.19―1.70; p  < 0.001; I 2  = 47.7%], pregestational diabetes [OR, 2.24; 95% CI, 1.21―4.12; p  < 0.010; I 2  = 56.3%], low paternal age [OR, 1.41; 95% CI, 1.10―1.81; p  = 0.007; I 2  = 0.0%], low birth weight [OR, 5.53; 95% CI, 1.95―15.70; p  = 0.001; I 2  = 98.5%], and neonatal female gender [OR, 1.54; 95% CI, 1.10―2.14; p  = 0.012; I 2  = 67.8%]. Conclusion: Stressful life events, pregestational diabetes, low birth weight, and neonatal female gender are risk factors associated with NTDs. Low maternal education level and low paternal age are factors that are moderately associated with NTDs. Further cohort studies are required to verify the factors associated with NTDs and control the risk of this severe birth defect.